Continuous versus intermittent noninvasive blood pressure measurement in patients with shock in prehospital emergency medicine – a single-center prospective pilot trial - Stephan Katzenschlager; Raphael Heck; Nikolai Kaltschmidt; Frank Weilbacher; Markus A. Weigand; Erik Popp; Maximilian Dietrich (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Shock is a critical and potentially life-threatening clinical state characterized by circulatory insufficiency and impaired micro- and macrocirculation. Rapid detection and initiation of therapy are essential for patient outcomes. In prehospital emergency medicine, assessment tools are limited, and intermittent noninvasive blood pressure (iNIBP) monitoring is the current standard of care. Recent findings suggest that this method may miss episodes of relevant hypotension. Continuous noninvasive blood pressure (cNIBP) and tissue oxygenation (StO2) measurements could improve the time to detection of shock. Methods This single-center prospective pilot trial compared a cNIBP system with standard iNIBP measurements in physician-staffed prehospital care. The study was conducted in the Rhine-Neckar region between May and December 2023. The Edwards HemoSphere system, including ClearSight for cNIBP and ForeSight for StO2, was used in conjunction with standard monitoring. Adults with shock were eligible for inclusion. Primary endpoint was the agreement between cNIBP and iNIBP; secondary endpoints included unrecognized hypotension (MAP < 60 mmHg) and comparison between cNIBP/iNIBP and StO2. Bland-Altman analysis quantified bias and limits of agreement (LoA). Results In total, 25 patients were included, resulting in 100 simultaneous measurements. iNIBP readings exceeded cNIBP measurements of mean arterial pressure (MAP) by 10.77 mmHg (p < 0.01). There were further significant differences for systolic and diastolic blood pressure, with higher values for iNIBP measurements. Bland-Altman analysis demonstrated systemic bias (MAP bias − 10.25) with wide LoA (-43.52 to 22.21), indicating poor interchangeability. In three out of 25 cases, standard intermittent blood pressure measurements failed to detect hypotension, although cNIBP showed MAP values below 60 mmHg. Conclusion Our pilot data show cNIBP and iNIBP values differ significantly, with clinical implications, potentially improving hemodynamic instability detection. However, as this is preliminary, more research on system reliability and benefits of enhanced monitoring is needed. Trial registration German Clinical Trials Registry (DRKS ID DRKS00031867) on 22.05.2023.